Heat and Mass Transfer Effects on Unsteady MHD Radiative Flow of a Chemically Reacting Fluid Past an Impulsively Started Vertical Plate (MATEMATIKA, 2014)
The interaction of free convection with thermal radiation of viscous in- compressible MHD unsteady chemical reacting ﬂuid ﬂow past an impulsively started vertical plate is analyzed. The Rosseland approximation is used to describe the ra- diative heat transfer in the limit of the optically thin ﬂuid. The non-linear, coupled equations are solved using an implicit ﬁnite diﬀerence scheme of Crank-Nicolson type. Velocity, temperature and concentration of the ﬂow have been presented for various parameters such as thermal Grashof number, mass Grashof number, Prandtl number, Schmidt number, radiation parameter and magnetic parameter. The local and average skin friction, Nusslet number and Sherwood number are also presented graphically. It is observed that, when the radiation parameter increases the velocity and temperature decrease in the boundary layer. Also, it is found that the presence of chemical reac- tion parameter leads to decrease in the velocity ﬁeld and concentration and rise in the thermal boundary thickness. Keywords : Heat transfer; MHD; Radiation; Finite-difference Scheme; Vertical plate 2010 Mathematics Subject Classiﬁcation 74A15